Local wisdom and tourism development in Kampung Nglanggeran, Gunung Kidul, Yogyakarta - Primantoro N Vitrianto (International Journal of Applied Sciences in Tourism and Events, 2023)
This research aims to examine the positive impact of local wisdom on environmental sustainability and tourism development. In this study, a qualitative approach was conducted through observations and interviews. This research has conducted the analysis using a descriptive ethnographic approach to reveal the meaning behind the local wisdom. The results show that being part of the UNESCO Global Geopark has special meaning for Gunung Sewu in Java, Indonesia. Geoparks are concerned with conserving and developing geological diversity and aiming to develop and conserve the cultures within them. Pitu village preserves local wisdom, one of which is the seven-family restriction. Local wisdom in this village is closely related to limited natural conditions. Kampung Pitu is located at the top of Mount Nglanggeran, and no more than seven families can live here because they have taboos or rules from the past. All the local wisdom carried out by the people of Kampung Pitu was based on preserving nature and the entire community's safety. The preservation of heritage will provide uniqueness and attract tourists on its own.